Skeptisisme Profesional Auditor dari Sudut Pandang Filsafat Jawa “Ojo Dumeh, Eling lan Waspodo” - Bhilawa, Loggar (Akuntansi: Jurnal Akuntansi Integratif, 2024)
This study aims to explore and analyze auditors' professional skepticism through the lens of Javanese philosophy, specifically the concepts of "Ojo Dumeh, Eling, and Waspodo." Professional skepticism, as the critical and cautious attitude of auditors in performing their duties, is linked to the values and teachings in Javanese philosophy to understand how these principles can enrich and deepen audit practice. The study's findings suggest a striking alignment between the ethos of audit professional skepticism and the Javanese philosophical concept of Ojo Dumeh, Eling lan Waspodo. In essence, audit professional skepticism embodies a mindset of critical inquiry and careful evaluation, mirroring Ojo Dumeh's call to avoid easy acceptance and instead verify information rigorously. The concept of Eling, emphasizing mindfulness and awareness, resonates with auditors' need for meticulous attention to detail. Likewise, Waspodo's emphasis on caution and prudence echoes the fundamental approach of auditors to exercise skepticism and maintain a cautious stance in their assessments. This correspondence underscores the universal value of critical thinking, careful scrutiny, and mindful deliberation across cultural and professional domains.